Incorporation of the Altered Cast Technique in the Fabrication Workflow of an Implant-Assisted Removable Partial Denture (IARPD) for an Elderly Patient - Dimokritos Papalexopoulos; Theodora-Kalliopi Samartzi; Panagiotis Tsirogiannis; Ioli-Ioanna Artopoulou; Nikitas Sykaras (Case Reports in Dentistry)
Implants are currently used to serve as abutments for implant-assisted removable partial dentures (IARPDs) to facilitate retention and support of the prosthesis. Implants are proposed in cases of posterior edentulous areas to convert Kennedy Class I or II to Class III or when the preparation of existing teeth to serve as abutments is contraindicated. The purpose of this report is to describe the protocol applied to fabricate an IARPD to restore a Kennedy Class II mandible of an elderly patient by incorporating traditional methods, such as the altered cast technique. Each step of the clinical procedure is thoroughly illustrated to document the selected appointment sequence. The patient was satisfied with the delivered prosthesis that demanded no additional implants to be placed but exploitation of an existing one. IARPDs are a viable and cost-effective solution substantiated by numerous reports with positive effects on patient satisfaction.